Male fertility in the least killifish, Heterandria formosa - gonopodia size does matter - Forssell, Mia (fi=Turun yliopisto|en=University of Turku|, 2018)
According to previous research, Heterandria formosa females mated to only one male had a fertility rate of less than 40%, whereas females mated to four males had a fertility rate of almost 90%. The aim of this study is to provide insight into reproductive mechanisms by studying the extent of male infertility, and a possible correlation between fertility and male- or gonopodium length in this species. Over the course of four weeks, each male (n=24) was consecutively mated to four virgin females (n=96). The females were then observed for fry production for circa 100 days, then lethally anaesthetised and photographed. The length of the fish and the males’ gonopodiums were then measured. Female fertility was 40.9%, male 62.5%. Gonopodium length (n=20) differed significantly (p=0.027) between fertile (6.19 mm ± 0.35) and infertile (5.72 mm ± 0.53) males, and correlated positively (p=0.034) with the number of females fertilized. Male length did not differ between fertile and infertile males, but there was a near significant (p=0.077) relationship between male length, and the number of fry a fertile female produced. Male infertility (of which gonopodium length is likely to be a factor) alone does not explain low fertility rates for monogamous matings. Sufficient gonopodium length seems essential in achieving successful fertilizations, and longer gonopodia are more efficient for achieving such (in laboratory conditions). The association between larger male size and a greater number of offspring under these conditions of sperm limitation would suggest, that larger males donate more sperm per female.